A REVISION OF THE TRIBE AELIINI (HEMIPTERA: PENTATOMIDAE: PENTATOMINAE) FROM THE INDO-PAKISTAN REGION (Journal of Sciences, Islamic Republic of Iran)
Five genera and ten species of the tribe Aeliini Still from the Indo-Pakistan region are keyed, compared to their closest allies and their geographical distribution given. A description of all the above genera and species of Adria St?l and Bonacialus Distant has been given. These species, including two new species of Adria, are described with special reference to their metathoracic scent gland complex and male and female genitalia